IMPLEMENTASI PROGRAM PEMBERDAYAAN PEREMPUAN DALAM MEWUJUDKAN KESETARAAN GENDER DI KABUPATEN KUTAI KARTANEGARA - Efri novianto; siti maimanah (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2014)
This research aimed to determine the implementation and the results achieved from the women's empowerment program in realizing gender equality in Kutai Kartanegara Regency. This type of research is qualitative deskriftif. Techniques used in determining the source of the data is Nonprobabilty Sampling by the method of Purposive Sampling. For the data collection Techniques used were participant observation, in-depth interviews, and study of the documentation. Data analysis techniques used to use interactive data analysis, as expressed by Miles and Huberman.Based on the results of the research can be inferred that the entire women's empowerment programs have been successfully implemented by the Agency for family planning, women's empowerment and child protection (BKBP3A) District of Kutai Kartanegara, just haven't managed to achieve gender equality in the district Kutai Kartanegara.Factors supporting the implementation of women's empowerment program in realizing gender equality in Kutai Kartanegara Regency, i.e. Regulation that support women's empowerment activities in realizing gender equality, namely Regulation of the Minister of Internal Affairs number 64 in 2011 and Regulation No. 52 Regent by 2013. While the factors restricting implementation of women's empowerment program is lack of budget allocated for financing women's empowerment program, quality of human resources in BKBP3A, limitations information, managing apparatus the attitude and lack of socialization. Kata Kunci : Implementation Program, Empowerment Of Women, Equality Gender